Casa en José Ignacio - Clusellas-Colle (2006)
Detalles constructivos sobre la vivienda que figura en la página 4 de la misma revista.
Keywords: CLUSELLAS, MARIANO; COLLE, SEBASTIÁN; URUGUAY; JOSÉ IGNACIO; VIVIENDAS UNIFAMILIARES